Succession planning and the sustainability of the land reform programme in Zimbabwe - Maunganidze, Langtone; Dzingirai, Vupenyu (SAGE Publications, 2022)
The influence of succession on organisational sustainability has been widely acknowledged globally, but studies focusing specifically on farms remain relatively limited. This article examines the factors influencing succession in the newly occupied farms under the fast track land reform programme in Zimbabwe and their implications for the sustainability of the land reform programme. The study followed a qualitative multi-case research design. Data were collected using a combination of unstructured interviews, informal discussions, lived experience narrations and direct observations. Notwithstanding other structural and institutional constraints, the absence of succession arrangements and the politics of survival have been found to be the major threats to sustainability.